IKEA: Go Green Eco Wardrobe / Muhammad Zikri Roslan - Roslan, Muhammad Zikri (2022)
Based on Wikipedia, IKEA is a Swedish multinational conglomerate that designs and sells ready-to-assemble furniture, kitchen appliances and home accessories, among other useful goods and occasionally home services. The main purpose of this company analysis is to investigate their backgrounds, strength and as well their weaknesses and along with the investigations, the final solutions can be achieved. The first problem regarding IKEA is the difficulties to standardize their wardrobes. Even though the company try its best to keep the key measure, this problem will always have possibilities to happen. Thus, some of the customers will get different wardrobes qualities. Aside from that, taking into accounts that raw materials and the cost of many inputs has risen lately, it is possible for the products to be likely impact the company, especially in term of their profits. When the production costs are high, it is adhered that the final products will have some problems since it is difficult to maintain the wardrobes replications due to increasing costs. The next weakness is environmental concerns due to IKEA uses millions of trees every year in order to expand their products worldwide. Non-recyclable wardrobe raw materials are a problem for IKEA. Since the organisation uses non-recyclable wood-based materials, our atmosphere will become hotter as the number of forest plots decreases and carbon dioxide absorbers decline. Along with the weaknesses, there will also be some solutions. One of the many things that could be enhanced is conducting a rigorous review and maintain strict quality control before the products are ready to be sold. Inspection equipment, which can include manual, electronic, and computerised machines, may be used to check materials, containers, and product components for conformance to the specification. As a result, the issue of non-standard and defective goods can be solved. The next solution is to conduct more Research and Development (R&D). Substitute other recyclable woods such as dimensional lumber and stumps for the readily available raw material (non-recyclable wood that has been covered with creosote). The new materials are conveniently recyclable, putting an end to environmental problems caused by timber logging.